A computational search for lipases that can preferentially hydrolyze long-chain omega-3 fatty acids from fish oil triacylglycerols. (15th April 2015) - Kamal, Md. Zahid; Barrow, Colin J.; Rao, Nalam Madhusudhana
Highlights: Omega-3 fatty acid containing triglycerides were docked on all lipases with known structure. Both non-covalent and covalent docking experiments were performed. Lipases showing preferences for omega-3 fatty acids were identified. Size of active sites was the major determinant of triglyceride selectivity. Abstract: Consumption of long-chain omega-3 fatty acids is known to decrease the risk of major cardiovascular events. Lipases, a class of triacylglycerol hydrolases, have been extensively tested to concentrate omega-3 fatty acids from fish oils, under mild enzymatic conditions. However, no lipases with preference for omega-3 fatty acids selectivity have yet been discovered or developed. In this study we performed an exhaustive computational study of substrate–lipase interactions by docking, both covalent and non-covalent, for 38 lipases with a large number of structured triacylglycerols containing omega-3 fatty acids. We identified some lipases that have potential to preferentially hydrolyze omega-3 fatty acids from structured triacylglycerols. However omega-3 fatty acid preferences were found to be modest. Our study provides an explanation for absence of reports of lipases with omega-3 fatty acid hydrolyzing ability and suggests methods for developing these selective lipases.